Novel Microsatellite Markers Discovery in Patagonian Toothfish (Dissostichus Eleginoides) Using High-Throughput Sequencing - Vidal-Soto, R; Touma-Lazo, J (Springer Netherlands, 2019)
Patagonian toohfish (Dissostichus eleginoides), is a sub Antartic notothenioid fish key in the marine ecosystem that sustains fishery of higher commercial value in the world. However, there are a scarce knowledge or information about its population genetic background, product of the almost null information of molecular markers available for this species. Here, we use high-throughput sequencing technology (Illumina platform) to develop 1071 microsatellite loci, of which 22 loci were selected to evaluation. Polymorphism and genetic diversity of each locus was assessed in two locations distant by 2370 km. Considering both locations, a mean PIC value of 0.748 was estimated. Selected microsatellite loci showed among two to seventeen alleles by locus in the first location and two to twelve in the second. The observed heterozygosity varied from 0.18 to 0.91 and from 0.12 to 0.87 for the first and second location, respectively. While, the expected heterozygosity ranged from 0.15 to 0.92 and from 0.11 to 0.90. Three loci were monomorphic in only one location. Microsatellite markers developed here will be useful in future studies on conservation, fishery and population genetics of this species. © 2019, Springer Nature B.V.